2011
DOI: 10.1186/1471-2164-12-513
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of seed-specific genes using digital differential display tools combined with microarray data from common wheat

Abstract: BackgroundWheat is one of the most important cereal crops for human beings, with seeds being the tissue of highly economic value. Various morphogenetic and metabolic processes are exclusively associated with seed maturation. The goal of this study was to screen and identify genes specifically expressed in the developing seed of wheat with an integrative utilization of digital differential display (DDD) and available online microarray databases.ResultsA total of 201 unigenes were identified as the results of DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This indicates that as early as 2 days after anthesis, marked transcriptional activity dedicated to the synthesis of nutrient components (storage proteins) occurs, together with the transcription of genes coding for protease-inhibitors and alpha-amylase inhibitors intended to protect these two components from degradation by different hydrolases. This finding is consistent with that of Yang et al, who identified these gene families as wheat seed-specific genes [ 52 ]. No enriched biological process was observed at the 240-260°Cdays transition.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This indicates that as early as 2 days after anthesis, marked transcriptional activity dedicated to the synthesis of nutrient components (storage proteins) occurs, together with the transcription of genes coding for protease-inhibitors and alpha-amylase inhibitors intended to protect these two components from degradation by different hydrolases. This finding is consistent with that of Yang et al, who identified these gene families as wheat seed-specific genes [ 52 ]. No enriched biological process was observed at the 240-260°Cdays transition.…”
Section: Discussionsupporting
confidence: 93%
“…These genes are protease inhibitors and protect cereal seed from attack by endogenous hydrolase. Thus, during the grain filling stage, in addition to the transcript accumulation of genes encoding storage proteins, genes involved in protecting the main nutritional resource of the developing seed from both endogenous and exogenous degradation are also active [ 52 ]. This phenomenon therefore appears to be important as it constitutes the significant change seen during the first transition (see above).…”
Section: Discussionmentioning
confidence: 99%
“…We found 436 transcripts (3.3%) that were over-expressed at least 10-fold in the resistant branch, while 970 transcripts (7.4%) were similarly over-expressed in the susceptible branch (Table 2). This difference compares to the variation in gene expression found between functionally distinct tissues in the same organism [29]. …”
Section: Resultsmentioning
confidence: 96%
“…The wheat embryo and endosperm samples from four germination periods were ground into fine powder in liquid nitrogen. Then, total RNA was extracted from each sample and reverse-transcribed into cDNA according to the procedures in Yang et al [ 86 ]. Gene-specific primers were designed using online Primer3Plus ( http://primer3.ut.ee/ ) according to Untergasser et al [ 87 ].…”
Section: Methodsmentioning
confidence: 99%